Liver resection after Transjugular Portosystemic Stent Shunt (TIPSS) - Sliwinski, Svenja; Trojan, Jörg; Mader, Christoph; Vogl, Thomas; Bechstein, Wolf (Zeitschrift für Gastroenterologie, 2022)
Hepatocellular carcinoma (HCC) often arises in cirrhotic livers. Generally, decompensated liver cirrhosis is a contraindication to surgery. Even in compensated liver cirrhosis, liver resection for HCC carries a high risk of post-hepatectomy liver failure and decompensation of cirrhosis. Thus, in current staging systems such as the Barcelona Classification of Liver Cancer (BCLC) or the Hong Kong Classification of Liver Cancer (HKLC), liver resection is limited to smaller tumors in compensated cirrhosis. While transjugular portosystemic stent shunts (TIPSS) are widely used for the treatment of complications of portal hypertension such as recurrent esophageal bleeding or refractory ascites, the presence of a TIPSS is generally considered a contraindication for liver resection. Herein, we describe – to our knowledge for the first time – liver resection of an intermediate HCC with a diameter of 11 cm in a patient who had previously received a TIPSS for decompensated cirrhosis. With open surgery, radical resection (R0) was able to be achieved, and the patient left the hospital after 6 days following an uncomplicated postoperative course. Thus, in highly selected cases, liver resection following TIPSS may be considered.
Keywords: transjugulärer portosystemischer Stent Shunt; hepatozelluläres Karzinom; Leberzirrhose; portale Hypertension; Leberresektion